Perubahan Sistem dan Praktik Hukum Pidana Indonesia Sebagai Akibat Berlakunya KUHP Baru - Sulistyani Eka Lestari; Fanny Tanuwijaya; Ferdricka Nggeboe; Asmak ul Hosnah; Deni Setya Bagus Yuherawan; Joice Soraya (Fakultas Hukum Universitas Islam Indonesia, 2024)
With the enactment of Law Number 1 of 2023 concerning the Criminal Code (New Criminal Code), there will be legal implications for several important aspects, namely the source of criminal law, the criminal justice system, and the practice of criminal law. This article aims to analyze predictions of implementing these 3 (three) aspects related to the provisions of Article 1 paragraph (1) and Article 2 of the New Criminal Code. In principle, Article 1 paragraph (1) of the New Criminal Code regulates the Principle of Legality, and Article 2 of the New Criminal Code regulates the existence and application of laws in society. The legal issue in this article is the potential difficulty of implementing 'living law'. It is necessary to substantially analyze several substantial things about the existence of the criminal law system and the criminal justice system that was formed with the enactment of Article 2 paragraph (1) of the New Criminal Code, as well as the potential juridical obstacles that exist in legal practice, with the existence of the newly formed criminal law system. This article uses legal research methods and doctrinal research types. This research uses a statutory approach and a conceptual approach. Analysis of legal materials uses prescriptive analysis with authentic and systematic interpretation. The analysis is intended to develop legal arguments regarding the juridical obstacles to enforcing 'laws that live in society.